Pencegahan Covid-19 Di Lingkungan Keluarga - Murwidi, Imam Cahyo; Muna, Lintal (AL-WARDAH: Jurnal Kajian Perempuan, Gender dan Agama, 2022)
Covid-19 is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This disease can be transmitted quickly by causing clinical manifestations from mild to severe and can even cause death. Efforts to prevent Covid-19 are the responsibility of all parties, including the government, society, families and individuals. Families have a very important role in preventing Covid-19 according to their roles and functions. The roles that families can play in preventing Covid-19 are as follows: (1) providing education to members about Covid-19 and its prevention measures, (2) providing the necessary facilities and infrastructure for the prevention of Covid-19, (3) implementing Covid-19 prevention health protocols in the family environment, (4) implementing a healthy lifestyle by exercising regularly and regularly, (5) consuming nutritionally balanced foods, (6) giving appreciation and emotional support to family members.